Prediction of patient admissions and bed requirement in inpatient department by using system dynamic simulation - Nazhatul Sahima Mohd Yusoff; Suriana Alias; Nor Maslina Mohamad Norsan; Nurhasnielaily Shamsuhaidi; Nursyaziela Rozalli (Penerbit Universiti Kebangsaan Malaysia, 2022)
Hospitals play a vital role in a nation’s healthcare system. As the custodian of primary healthcare providers, hospitals strive to provide continuous and comprehensive care to patients. The increase of patients annually sparked the requirement for the hospitals to reasonably plan and project their resources especially treatment beds with the goal to meet the uprising patient’s demand. A similar predicament is also encountered by one of the busiest public hospitals in Selangor, Malaysia. The spike in patients’ demand has reflected in the hospital’s struggle in embracing the rapid changes while providing the best quality health care. Therefore, this study focuses on the hospital’s inpatient department which requires accurate resource planning and precise allocation of treatment beds. Hence, the system dynamics simulation modelling is developed to enable the prediction of the number of inpatient admission and the total number of treatment beds required to meet the demand at the hospital for a period of ten years. The study’s findings revealed an increase in inpatient admission and roughly one bed is required to be added approximately every two years in pursuance to meet the demand. Conclusively, the surge in the inpatient’s admission will parallelly increase the use of treatment beds by the patients. The results formulated by this study will enable the hospital management’s decision making in terms of managing, planning and predicting of resources within their allocated budget while ensuring the betterment of service quality and enhancing the performance of the inpatient department.